UPAYA GURU DALAM MENINGKATKAN KEDISIPLINAN SISWA KELAS VB DI SD 02 PARIT MERDEKA KECAMATAN TANGARAN TAHUN PELAJARAN 2024-2025 - Filzah; Astaman; Mauizatul Hasanah (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to uncover: 1) Teacher planning to improve discipline among first-grade students at SDN 02 Parit Merdeka, Tangaran District, in the 2023-2024 academic year; 2) Teacher implementation in improving discipline among first-grade students at SDN 02 Parit Merdeka, Tangaran District, in the 2023-2024 academic year; 3) Teacher evaluation in improving discipline among first-grade students at SDN 02 Parit Merdeka, Tangaran District, in the 2023-2024 academic year. This study uses a qualitative approach and is descriptive in nature. Data collection techniques include interviews, observation, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing. Data validity checks include triangulation and member checking. The results of the study: 1) Teacher planning to improve the discipline of class VB students at SDN 02 Parit Merdeka, Tangaran District, in the 2023-2024 academic year, namely habituation, role model, awareness, and supervision. 2) Teacher implementation in improving the discipline of class VB students at SDN 02 Parit Merdeka, Tangaran District, in the 2023-2024 academic year, namely preventive implementation, repressive implementation, and curative implementation. 3) Teacher evaluation in improving the discipline of class VB students at SDN 02 Parit Merdeka, Tangaran District, in the 2023-2024 academic year, namely obeying school regulations, giving rewards, consistency in giving rewards, and motivation.